Effectiveness of Om chanting on perceived stress, negative affectivity, and social inhibition in individuals with pre-hypertension - Chokkan, Deepa; Bhel, Ashish; Kalyani T,; Ramesh P, (Asian Journal of Medical Sciences, 2024)
Background: Akara, Ukara, Makara (OUM) chanting regulates emotions and removes negative emotions by inactivating the processing in the amygdala. At the same time, the prefrontal complex was inhibited followed by chanting OUM. Further, there was an increase in the oxygenation levels followed by chanting OUM. Hence, OUM chanting has multiple benefits and offers improvement in the quality of life. Though there are multiple benefits followed by chanting OUM, the scientific evidence for the same is comparatively less. Hence, there is a need for more studies in this area. Aims and Objectives: The present study aimed to find out the variations in the perceived stress, negative affectivity, and social inhibition in pre-hypertensive individuals and also to observe the effectiveness of Om chanting on perceived stress, negative affectivity, and social inhibition in pre-hypertensive individuals. Materials and Methods: The present study was conducted at the St Peter’s Medical College Hospital and Research Institute, Hosur, Tamil Nadu, India. A total of 50 young adults with pre-hypertension were recruited in the study after obtaining written informed consent. Age- and gender-matched 50 healthy participants were recruited after obtaining the voluntary, informed consent. Diamond digital sphygmomanometer was used to record the blood pressure. All the parameters were recorded at 9 am for the convenience of the participants and also to avoid diurnal variation. The perceived stress scale was used to assess the stress levels. Negative affectivity and social inhibition were recorded using a type D (DS-14) questionnaire. Cases practiced the OUM chanting for 6 weeks after they were trained by an expert yoga therapist. Results: Perceived stress scores were significantly decreased followed by the OUM chanting. There was a significant decrease in the scores of negative affectivity of cases after the intervention when compared with control group participants. There was a significant decrease in the scores of social inhibition of cases after the intervention when compared with control group participants. Conclusion: Perceived stress, negative affectivity, and social inhibition were significantly higher in the pre-hypertensive individuals. The study results provide further evidence that practicing OUM chanting causes stress relief and also decreases the negative emotions that is negative affectivity and social inhibition in pre-hypertensive individuals.